Method for synthesizing sodalite from 4A zeolite and synchronously solidifying radioactive waste salt in situ
By synthesizing 4A zeolite and sodaite and sintering at high temperature, a sodaite curing solids are formed, and radioactive waste salts are cured simultaneously in situ, solving the problems of low treatment efficiency and unstable curing of spent fuel waste salts in the prior art, and achieving efficient and safe curing and fixing of radioactive waste salts.
Patent Information
- Application Number
- CN202411940643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing spent fuel waste salt treatment methods have complex operation, high cost, low treatment efficiency and possible secondary pollution problems, especially the difficulty in effectively curing and fixing lobe elements and chlorine elements in radioactive waste.
By synthesizing 4A zeolite and sodaite and sintering at high temperature, a sodaite solidified body is formed, and the radioactive waste salt is cured simultaneously in situ. The porous structure of 4A zeolite and the lattice structure of sodaite are used to embed or adsorbed into the cured body.
The efficient curing and fixation of radioactive waste salts is achieved, and the risk of migration, diffusion and leakage of radioactive elements is reduced. The process operation is simple, energy consumption is low, and the amount of cured substrate is low.
Smart Images

Figure CN119683639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of radioactive waste salt solidification treatment in spent fuel dry post-processing, and in particular to a method for synthesizing sodalite with 4A zeolite and in-situ synchronously solidifying radioactive waste salt. Background Art
[0002] Nuclear energy is used worldwide due to its high energy density, low carbon footprint and low electricity cost. However, with the rapid development of the nuclear energy industry, efficient and safe spent fuel salt treatment technology is one of the keys to achieve the recycling of fast reactor spent fuel and the complete disposal of spent salt. Traditional spent fuel salt treatment methods, such as wet treatment, have problems such as complex operation, high cost, low treatment efficiency and possible secondary pollution. Among the current spent fuel salt treatment methods, the most promising one is dry post-processing technology. Dry post-processing technology mainly involves molten salt electrolytic refining and reduction treatment, the purpose of which is to extract valuable materials from used nuclear fuel, and also produces a certain amount of radioactive waste. LiCl-Li2O waste salt, as one of the by-products of the electrolytic reduction process, mainly includes fragmented elements (including Cs, Sr, Ba, Ce, etc.) and chlorine elements, which are highly water-soluble and radioactive, have strong migration and transformation capabilities in the environment, are difficult to be captured and fixed, and improper disposal will cause harm to the environment. Therefore, the proper treatment of radioactive waste remains challenging.
[0003] Among the many post-processing technologies, solidification and stabilization technology is an effective strategy. The solidified body formed can not only prevent the migration of radioactive nuclides, but also establish a natural barrier to block radioactivity. As for the fixed and stabilized materials, they must have the characteristics of chemical resistance, heat resistance, radiation resistance, hydrolysis resistance, and low radioactive nuclide leaching rate. Traditional immobilization materials, such as cement and asphalt, have poor thermal and radiation stability and can only be applied to low-level liquid wastes. In addition, vitrification and asphalt immobilization technologies consume a lot of energy and have low solubility for fission elements in the form of chlorides, and the required sintering temperature is higher than 1000 °C, which can easily cause the target nuclides to volatilize and escape. Therefore, the development of stabilized materials that can effectively capture radioactive fragment elements and chlorine elements from radioactive waste liquids, molten salts, and solid waste salts and fix them in the structure of inorganic materials is crucial to reducing energy consumption, simplifying the radioactive waste treatment process, and safely disposing of them.
[0004] Artificial rock solidification technology uses environmentally friendly and low-cost materials to synthesize artificial rocks through optimized ratios. It can embed fragment elements and chlorine elements in waste salt into the crystal lattice of mineral phases or adsorb them inside and outside the skeleton structure, etc., to achieve targeted capture of different fragment elements and solidification by isomorphous substitution, and convert waste salt into a harmless solid form with strong thermal stability, radiation stability, chemical stability and geological stability, thereby improving the stability of radioactive nuclides in artificial rock solidification and effectively reducing the risk of migration and diffusion of radioactive substances.
[0005] Natural minerals such as sodalite and perovskite are used for long-term fixation of radionuclides. They have excellent chemical and mechanical stability and low nuclide leaching rate. Among them, sodalite can embed fragmentation elements and chlorine elements into the sodalite lattice at the same time. It shows good long-term safety under deep geological disposal conditions. Considering the solidification process, cost, mechanical strength, chemical stability and normalized leaching rate, sodalite is considered to be the preferred mineral-based material for solidifying fragmentation elements and chlorine elements.
[0006] Sodalite (Na8Al6Si6O 24 Cl2) is a chloride-containing sodium aluminum silicate mineral, which belongs to a class of feldspar-like minerals. Its crystal structure belongs to the P-43n cubic space group, and the basic structural unit is a β cage. AlO4 and SiO4 tetrahedrons are connected together by sharing oxygen atoms to form four-membered rings and six-membered rings. These four-membered rings and six-membered rings are further spliced into an aluminosilicate skeleton structure with a diameter of 6.5 Å through sharing edges to form a β cage. The six-membered ring size of the β cage is about 2.6 Å, which allows some ions to pass through and provides an effective diffusion path for the ions in the cage. By sharing four-membered rings, the β cages are stacked in a simple cubic array. The four Na + Located in the β cage, it combines with the anion in the center of the cage to form a tetrahedron, Na + Located on the central axis of the six-membered ring, Cl - Located at the 2a site in the center of the β cage, its special porous structure and ion exchange capacity can fix metal ions inside the cage structure, inhibit their diffusion, and achieve the purpose of nuclide solidification.
[0007] In summary, the present invention provides a sodalite solidified body and a solidification method thereof, which has low synthesis energy consumption, simple process operation, small amount of solidified substrate, large radioactive waste salt coverage rate, high fixed amount of radioactive element chloride, stable geological storage, and greatly reduces the harm of radioactive elements in radioactive waste salt to the environment. Summary of the invention
[0008] In view of the above shortcomings of the prior art, the present invention provides a method for synthesizing sodalite with 4A zeolite and simultaneously solidifying radioactive waste salt in situ. By using a small amount of 4A zeolite, more radioactive waste salt can be converted into a stable and harmless solid form, which is conducive to long-term geological storage and effectively reduces the migration, diffusion and leakage risks of radioactive substances.
[0009] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0010] A method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ comprises the following steps:
[0011] (1) mixing solid raw materials including 4A zeolite powder, radioactive waste salt, and alkali metal chloride salt with a dispersant in a certain liquid-solid ratio, and then heating and drying to obtain a solidified precursor; wherein the mass ratio of the 4A zeolite to the alkali metal chloride is (3-5):1; and the mass percentage of the radioactive waste salt in the total weight of the solid raw materials is 15%-45%;
[0012] (2) Grinding, sieving, and sintering the solidified precursor to obtain a sodalite solidified body.
[0013] The mechanism of the present invention for synthesizing sodalite and in-situ simultaneous solidification of radioactive waste salt is to control the content of sodalite and nepheline in the sodalite solidified body by regulating the proportion of 4A zeolite powder and alkali metal chloride salt in the solid raw material and controlling the sintering temperature, and to combine lattice solidification, adsorption, chemical coordination, ion exchange and other processes to make the fragment elements and chlorine in the radioactive waste salt more embedded in the artificial rock skeleton, lattice or adsorbed inside and outside the structure, so as to achieve targeted capture of a large number of different elements and lattice solidification of isomorphous substitution, thereby converting all radioactive waste salt into a stable and harmless solid form, which is conducive to long-term geological storage and effectively reduces the migration, diffusion and leakage risks of radioactive elements in radioactive waste salt. According to calculations, in the sodalite solidified body of the present invention, the fixed amount of radioactive element chloride is as high as 5.061% to 15.183%.
[0014] Furthermore, the radioactive waste salt includes radioactive waste salt of electrolytic reduction salt LiCl-Li2O system or electrolytic refining salt LiCl-KCl system.
[0015] The present invention adopts an appropriate proportion of alkali metal chloride salt to reduce the amount of 4A zeolite, and mixes 4A zeolite powder, radioactive waste salt, and alkali metal chloride salt with a solidified precursor at a specific temperature, and controls the sintering temperature and the amount ratio of 4A zeolite powder, radioactive waste salt, and alkali metal chloride salt to control the sodalite solidified body obtained by sintering to be a sodalite-nepheline mixture.
[0016] The radioactive waste salt involved in the present invention includes radioactive waste salt of LiCl-Li2O system or electrolytic refined salt LiCl-KCl system, and its residue contains Cl, Li and other elements required for synthesizing sodalite, wherein Li can replace the site of Na and enter the lattice structure of sodalite; on the other hand, alkaline earth metals such as Sr can occupy the elementary structure of sodalite AlSiO4, therefore, the method provided by the present invention has its own advantages in solidifying chloride waste salt system. The present invention utilizes the characteristic that alkali metal chloride salts usually have good water solubility or dispersibility, and prepares a waste salt solidification precursor solution by mixing radioactive waste salt of LiCl-Li2O system or electrolytic refined salt LiCl-KCl system with alkali metal chloride salt and 4A zeolite in water, and then evaporates the water to obtain a solidification precursor for synthesizing sodalite, and synthesizes sodalite through high temperature synthesis and sintering process. The present invention adopts radioactive waste salt, 4A zeolite (Na 12 (AlSiO4) 12 ) and alkali metal chloride salt (XCl) are used to synthesize sodalite solidified body, and the reaction formula is as follows:
[0017] Na 12 (AlSiO 4 ) 12 + (4-nx)XCl + n MCl → 2Na (8-nx) M n Al 6 Si 6 O 24 Cl 2
[0018] The invention analyzes the composition and characteristics of radioactive waste salt residue, uses 4A zeolite, alkali metal chloride salt and radioactive waste salt as raw materials, utilizes the uniform dispersion characteristics of a dispersant in an open system and at a specific temperature to prepare a solidification precursor, synthesizes a sodalite solidified body in situ at high temperature, explores the influence of condition parameters (temperature, time, coverage rate, pressure) and the like in the process of synthesizing the sodalite solidified body on the synthesis of the sodalite solidified body and the solidification of the radioactive waste salt, further evaluates the effect and action mechanism of the sodalite solidified body on the radioactive elements by means of material characterization means and normalized leaching rate experiments, provides theoretical support for synthesizing a new type of sodalite solidified material, provides a basis for simulating the solidification of radioactive waste salt, helps to establish a sodalite solidified body synthesis technology and a safe application procedure in waste salt treatment and disposal, and provides technical guidance for the practical application of the technology in the field of industrial radioactive waste salt solidification.
[0019] Furthermore, in step (1), the particle size of the 4A zeolite powder is within 1 nm.
[0020] Furthermore, in step (1), the alkali metal chloride salt is one or more of lithium chloride (LiCl), sodium chloride (NaCl), and potassium chloride (KCl).
[0021] Furthermore, in step (1), the dispersant is one or more of water, ethanol and acetone.
[0022] Furthermore, in step (1), the liquid-to-solid ratio of the solid raw material to the dispersant is (4-6):1.
[0023] Furthermore, in step (1), the heating treatment is performed at a temperature of 60 to 100 °C and for a time of 6 to 12 h.
[0024] Furthermore, in step (1), the drying temperature is 100°C and the drying time is 15 to 30 hours.
[0025] Furthermore, in step (2), the sintering temperature is 600-900°C and the sintering time is 2-12 h.
[0026] Furthermore, in step (2), during the sintering, the solidified precursor powder is placed in a mold and pressed into a block under a pressure in the range of 30-70 MPa.
[0027] Furthermore, in step (2), the sintering is carried out in an inert gas atmosphere and is divided into the following three steps: the first step is heating, with a heating rate of 5 °C / min, to a target temperature of 600-900 °C; the second step is heat preservation, at 600-900 °C for 2-12 h; the third step is cooling, with a cooling rate of 5 °C / min, to obtain a sodalite solidified body after cooling to room temperature.
[0028] Furthermore, the method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ comprises the following specific steps:
[0029] (1) 4A zeolite was ball-milled at 200 r / min for 4 h with a ball-to-material ratio of 10:1 and passed through a 0.1 nm sieve to obtain a powder;
[0030] (2) Preparation of curing precursor: 4A zeolite powder, radioactive waste salt, alkali metal chloride salt and dispersant were mixed evenly at a liquid-to-solid ratio of (4-6):1, and heated in a 75 ℃ water bath with magnetic stirring at 200 r / min for 8 h. The obtained slurry was dried in an oven at 100 ℃ for 15-30 h to obtain a curing precursor;
[0031] (3) High-temperature sintering: Grind the solidified precursor in an agate mortar for 30 min and then pass it through a 0.1 mm sieve. Sinter the powder at a sintering temperature of 600-900 °C for 2-12 h to obtain a sodalite solidified body.
[0032] Compared with the prior art, the present invention is beneficial in that:
[0033] 1. The present invention aims at the problem that the existing LiCl-Li2O system or electrolytic refined salt LiCl-KCl system radioactive waste salt solidification technology cannot efficiently and stably solidify radioactive elements (there are problems that fragmented elements and chlorine elements are easy to migrate and difficult to capture), and provides a sodalite waste salt solidification method that is economical, environmentally friendly, low in energy consumption, simple in operation process, safe and reliable, chemically stable, and can meet the requirements of long-term stable disposal of radioactive waste. The sodalite solidified body of the present invention uses a small amount of solidification base material (a small amount of 4A zeolite), and at the same time, the radioactive waste salt has a large coverage rate and can be stored stably for a long time. The method provided by the present invention has considerable economic and ecological benefits, and the method is suitable for the field of radioactive waste adsorption and immobilization in aqueous solution, molten salt base, and solid waste salt.
[0034] 2. Compared with the existing glass or ceramic solidification technology, the raw materials of the method provided by the present invention are easily available, economical and environmentally friendly, the operation process is simple, and there is no secondary pollution problem; in addition, the dissolution compatibility of the splinter element and the chlorine element is good, and the waste salt inclusion rate is as high as 45%. The synthesized sodalite solidified body has strong thermal stability and high mechanical hardness. The normalized leaching rate after immersion in 90 ° C water for 28 days is less than 5 x 10 -4 g / (cm 2 d), can be stored stably for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 SEM and EDS images of 4A zeolite;
[0036] Figure 2 This is the XRD phase analysis result diagram of 4A zeolite and solidified precursor;
[0037] Figure 3 This is a graph showing the XRD phase analysis results of sodalite solid bodies synthesized at different sintering temperatures in Example 1;
[0038] Figure 4 This is a diagram showing the XRD phase analysis results of the sodalite solidified body synthesized using different sintering times in Example 2;
[0039] Figure 5 This is a graph showing the XRD phase analysis results of sodalite solidified bodies synthesized using different mass percentages of radioactive waste salts in Example 3;
[0040] Figure 6 This is an XRD phase analysis result diagram of the product of the sodalite solidified body synthesized by using different mass percentages of radioactive waste salt in Example 3 after being soaked in 90° C. water for 28 days;
[0041] Figure 7 The Fourier transform infrared spectra of 4A zeolite, solidified precursor and synthesized sodalite solidified body in Example 3;
[0042] Figure 8 The specific surface area and pore size analysis results of the 4A zeolite and the synthesized sodalite solidified body in Example 3;
[0043] Fig. 9 TG and DSC results of the solidified precursor and the synthesized sodalite solidified body in Example 3;
[0044] Fig.10 Schematic diagram of the two-step high-temperature short-time sintering in Example 4;
[0045] Fig.11 The density and porosity test results of the sodalite solid body synthesized in Example 4;
[0046] Fig.12 The hardness test results of the sodalite solidified body synthesized in Example 4 are shown in FIG. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The present invention provides a method for synthesizing sodalite from 4A zeolite and in-situ synchronously solidifying radioactive waste salt, comprising the following steps:
[0049] (1) mixing solid raw materials including 4A zeolite powder, radioactive waste salt, and alkali metal chloride salt with a dispersant in a certain liquid-solid ratio, and then heating and drying to obtain a solidified precursor; wherein the mass ratio of the 4A zeolite to the alkali metal chloride is (3-5):1; and the mass percentage of the radioactive waste salt in the total weight of the solid raw materials is 15%-45%;
[0050] (2) Grinding, sieving, and sintering the solidified precursor to obtain a sodalite solidified body.
[0051] In some examples, the radioactive waste salt includes radioactive waste salt from an electrolytic reduction salt LiCl-Li2O system or an electrolytic refining salt LiCl-KCl system.
[0052] In some examples, the liquid-to-solid ratio of the solid raw material to the dispersant is (4-6):1.
[0053] In some examples, the alkali metal chloride salt is one or more of LiCl, NaCl, and KCl.
[0054] In some examples, the dispersant is one or more of water, ethanol, and acetone.
[0055] In some examples, the heating treatment is performed at a temperature of 60 to 100° C. and for a time of 6 to 12 hours.
[0056] In some examples, the sintering temperature is 600-900° C. and the sintering time is 2-12 h.
[0057] In some examples, during the sintering, the solidified precursor powder is placed in a mold and pressed into a block at a pressure in the range of 30-70 MPa.
[0058] In the following specific embodiments, the 4A zeolite has a purity of 99% and is purchased from Sinopharm; the alkali metal chloride salt is sodium chloride with a purity of 99% and is purchased from Sinopharm; the radioactive waste salt is a simulated LiCl-Li2O system radioactive waste salt, comprising the following components in mass percentage: 32.76% LiCl, 33.50% Li2O, 12.56% CsCl, 11.13% BaCl2, 6.36% SrCl2, and 3.69% CeCl3; see Table 1 for details; wherein, the LiCl has a purity of 99% and is purchased from Sinopharm; the Li2O has a purity of 99% and is purchased from Sinopharm; the BaCl2 has a purity of 99% and is purchased from Sinopharm; the CsCl has a purity of 99% and is purchased from Aladdin; the SrCl2 has a purity of 99% and is purchased from McLean; and the CeCl3 has a purity of 99% and is purchased from Sinopharm.
[0059] Table 1: Composition of simulated radioactive waste salt
[0060]
[0061] In the following specific examples, Cu Ka radiation (λ = 1.5418A) was used to perform X-ray diffraction (XRD) on the sintered product for phase identification, operating at 60 kV and 55 mA, with a scanning parameter of 10 o -70 o , with a step size of 0.002.
[0062] In the following specific examples, the microstructure and morphology of 4A zeolite were observed using a scanning electron microscope (SEM, Zeiss SIGMA) equipped with an energy dispersive spectrometer (EDS, Oxford X-max 55).
[0063] In the following specific examples, the functional groups of 4A zeolite, the solidified precursor and the synthesized sodalite were tested by Fourier transform infrared spectroscopy (FTIR). The 4A zeolite, the solidified precursor and the synthesized sodalite were pressed into tablets with KBr, and the spectral range of 400-4000 cm -1 Detection within the range with a resolution better than 0.4 cm -1 , beam accuracy better than 0.01 cm -1 .
[0064] In the following specific examples, the concentrations of ions (Cs, Ba, Sr, Ce) in the leaching solution of the sintered product were measured by inductively coupled plasma mass spectrometry (ICP-MS, PQ-MS).
[0065] In the following specific examples, the specific surface area and pore size of the sodalite solid body were tested by a fully automatic specific surface and porosity analyzer (BET, Micromeritics ASAP 2460). Before the test, the sodalite solid body was degassed at 300° C. for 4 h.
[0066] In the following specific examples, the thermal stability of the samples was measured by a synchronous thermal analyzer (HITACHI STA200) under an Ar atmosphere from room temperature to 900° C. at a heating rate of 5° C. / min.
[0067] Example 1
[0068] A method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ, comprising the following steps:
[0069] S1. Ball mill 4A zeolite at 200 r / min for 4 h with a ball-to-material ratio of 10:1, and pass through a 0.1 nm sieve to obtain powder. Figure 1 The SEM / EDS image shows the structure and element distribution of 4A zeolite. It can be seen from the figure that the ratio of Al to Si in 4A zeolite is close to 1:1.
[0070] S2. Mix 15% by mass of radioactive waste salt with 4A zeolite powder, sodium chloride and water at a liquid-solid ratio of 5:1, wherein the mass ratio of 4A zeolite powder to sodium chloride is 4:1. Heat the mixture in a 75°C water bath at 200 r / min for 8 h, and dry the slurry in a 100°C oven with air blast for 24 h after evaporation of water to obtain a solidified precursor. Figure 2The XRD phase analysis results showed that the solidification precursor phases were mainly sodium chloride salt and type A zeolite aluminosilicate, indicating that the solidification precursor was basically consistent with the raw materials and no new phase was generated.
[0071] S3. Grind the solidified precursor in an agate mortar for 30 min and then pass it through a 0.1 mm sieve. Use a muffle furnace in an Ar atmosphere and normal pressure to maintain the solidified precursor powder at 600, 650, 700, 750, 800, 850 and 900 °C for 2 h, respectively. The heating and cooling rates are both 5 °C / min to obtain a sodalite solidified body.
[0072] Figure 3 The XRD phase analysis results show that the sodalite solidified body obtained at a sintering temperature below 800 ℃ is mainly composed of aluminosilicate, while the sodalite solidified body obtained at a sintering temperature of 800 ℃ and above is mainly composed of sodalite phase.
[0073] Example 2
[0074] A method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ, comprising the following steps:
[0075] S1. Ball mill 4A zeolite at 200 r / min for 4 h with a ball-to-material ratio of 10:1, and pass through a 0.1 nm sieve to obtain powder.
[0076] S2. Mix 15% by mass of radioactive waste salt with 4A zeolite powder, sodium chloride and water at a liquid-solid ratio of 5:1, wherein the mass ratio of 4A zeolite powder to sodium chloride is 4:1. Heat the mixture in a 75°C water bath at 200 r / min for 8 h, and dry the slurry in a 100°C oven with air blast for 24 h after evaporation of water to obtain a solidified precursor.
[0077] S3. Grind the solidified precursor in an agate mortar for 30 min and then pass it through a 0.1 mm sieve. Use a muffle furnace to sinter the solidified precursor powder at 800 °C for 1, 2, 4, 6, 8, and 10 h in an Ar atmosphere and normal pressure. The heating and cooling rates are both 5 °C / min to obtain a sodalite solidified body.
[0078] Figure 4 The XRD phase analysis results show that the phase of the sodalite solid body obtained with sintering time of 2 and 4 h is sodalite phase; the phase of the sodalite solid body obtained with sintering time of 8 and 10 h is a mixed phase of sodalite phase and nepheline phase.
[0079] Example 3
[0080] A method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ, comprising the following steps:
[0081] S1. Ball mill 4A zeolite at 200 r / min for 4 h with a ball-to-material ratio of 10:1, and pass through a 0.1 nm sieve to obtain powder.
[0082] S2. Radioactive waste salts with mass percentages of 15%, 25%, 35% and 45% were mixed with 4A zeolite powder, sodium chloride and water at a liquid-solid ratio of 5:1, wherein the mass ratio of 4A zeolite powder to sodium chloride was 4:1. The mixture was heated in a 75 ℃ water bath at 200 r / min for 8 h with magnetic stirring, and the slurry after evaporation of water was dried in a 100 ℃ oven for 24 h to obtain a solidified precursor.
[0083] S3. Grind the solidified precursor in an agate mortar for 30 min and then pass it through a 0.1 mm sieve. Use a muffle furnace to sinter the solidified precursor powder at 800 °C for 2 h in an Ar atmosphere and normal pressure. The heating and cooling rates are both 5 °C / min to obtain a sodalite solidified body.
[0084] The sodalite solidified body synthesized in this embodiment has a solidified amount of radioactive element chloride as shown in Table 2.
[0085] Table 2: Solidified amount of radioactive elements in the sodalite solidified body synthesized in Example 3
[0086]
[0087] Figure 5 The XRD phase analysis results of sodalite solids prepared by using different mass percentages of radioactive waste salts show that when the mass percentage of radioactive waste salts is 15%, the phase of the obtained sodalite solids is mainly sodalite phase; when the mass percentage of radioactive waste salts is 25%, 35%, and 45%, the obtained sodalite solids are a mixture of sodalite and nepheline. Figure 6 The XRD phase analysis results of the sodalite solidified bodies prepared by using different mass percentages of radioactive waste salts after being immersed in a 90 ℃ water bath for 28 days show that the phase of the sodalite solidified bodies after immersion is consistent with that before immersion, and no new phase is generated, indicating that the sodalite solidified bodies of the present invention have high structural stability in a hydrothermal environment.
[0088] The sodalite solidified bodies synthesized with radioactive waste salt mass percentages of 15% and 25% in Example 3 were subjected to infrared characterization analysis. The results are as follows: Figure 7 shown. Figure 7 The characteristic peaks of sodalite Al-O-Si typical of the synthesis are shown in the wavenumber. Figure 8The specific surface area and pore size analysis of the sodalite solidified body synthesized by 4A zeolite and 15% by mass of radioactive waste salt indicate that the sodalite solidified body synthesized by the present invention is a mesoporous material. The figure shows that the adsorption and desorption curves of the sodalite solidified body are closed and cross negative values appear, indicating that the specific surface area of the synthesized sodalite solidified body itself is smaller and denser; and the surface area decreases from 4A zeolite to sodalite solidified body because the sodalite solidified body synthesized by the present invention itself is denser and the metal ions fill and occupy its pores during the synthesis process.
[0089] Table 3 shows the calculation results of the unit cell parameters of sodalite solidified bodies synthesized with 15% and 25% radioactive waste salt mass percentages. The contraction of the unit cell parameters further proves that Li + Replaced Na + Enter into the lattice structure of the sodalite solid body.
[0090] Table 3: Calculation results of unit cell parameters of sodalite solid body
[0091]
[0092] The normalized leaching rate of the sodalite solid body obtained in Example 3 was evaluated as follows: the sodalite solid body was ground in an agate mortar for 30 min, passed through a 100-200 mesh sieve, 1 g of powder was put into a reactor, 10 mL of deionized water was added and the mixture was immersed at a constant temperature of 90 °C. On the 28th day, the ion concentration in the leachate was determined by inductively coupled plasma mass spectrometry (ICP-MS) to calculate the normalized leaching rate.
[0093] The normalized leaching rate is calculated according to the following formula:
[0094]
[0095] Among them, NL i is the normalized leaching rate, in gm -2 d -1 ; C i is the mass concentration of element i in the leachate, in gm -3 ; V is the volume of the leachate, in m 3 ;f i is the mass fraction of element i in the solid body; SA is the total surface area of the particles, in m 2 ; t is the soaking time, unit is d.
[0096] After the sodalite solidified powder was immersed in 90 ℃ water for 28 days, the normalized leaching rates of the four splinter elements Cs, Sr, Ba, and Ce were all less than 5 x 10 -4 g / (cm 2·d), the results show that the phase of the sodalite solidified body synthesized by the method of the present invention is a mixture of sodalite phase and nepheline phase, which can effectively solidify the fragment elements in the radioactive waste salt, which is beneficial to long-term geological storage. At the same time, the inventors found that after the sodalite solidified body synthesized by sintering time of 8 h in Example 2 was immersed in 90 ℃ water for 28 days, the normalized leaching rate of the four fragment elements Cs, Sr, Ba, and Ce was at least 7.5 x10 -4 g / (cm 2 ·d).
[0097] Evaluation of thermal stability of sodalite solidified body:
[0098] The sodalite solidified body synthesized from 15% by mass of radioactive waste salt in Example 3 was subjected to thermogravimetric analysis (TG) and differential scanning calorimetry (DSC, peaks pointing downward are positive). The results are as follows: Fig. 9 shown. Fig. 9 The results show that the precursor loses weight due to water within 200℃, 200~800℃ corresponds to the phase transformation process of the raw material synthetic sodalite solid body, and there is an endothermic peak at 750~800℃, which corresponds to the endothermic process of the synthetic sodalite solid body; while the synthesized sodalite solid body remains stable within 700℃, and begins to lose weight above 800℃, which corresponds to the volatilization of LiCl in the sodalite solid body, indicating that the sodalite solid body has good thermal stability. In addition, the inventors have found that the sodalite solid bodies synthesized with mass percentages of 25%, 35%, and 45% also have good thermal stability within 800℃.
[0099] Example 4
[0100] A method for synthesizing sodalite from 4A zeolite and simultaneously solidifying radioactive waste salt in situ, comprising the following steps:
[0101] S1. Ball mill 4A zeolite at 200 r / min for 4 h with a ball-to-material ratio of 10:1, and pass through a 0.1 nm sieve to obtain powder.
[0102] S2. Mix 25% by mass of radioactive waste salt with 4A zeolite powder, sodium chloride and water at a liquid-solid ratio of 5:1, wherein the mass ratio of 4A zeolite powder to sodium chloride is 4:1. Heat the mixture in a 75°C water bath at 200 r / min for 8 h, and dry the slurry in a 100°C oven with air for 24 h after evaporation of water to obtain a solidified precursor.
[0103] S3, the solidified precursor was ground in an agate mortar for 30 min and then passed through a 0.1 mm sieve. It was sintered in an Ar atmosphere at 30, 40, 50, 60, and 70 MPa using a two-step high-temperature short-time sintering method (e.g. Fig.10 During sintering, due to the poor conductivity of the solidified precursor powder, in this embodiment, 2 g of the solidified precursor powder was wrapped with carbon paper (thickness of 0.1 mm) and placed in a mold (inner diameter of 15 mm, outer diameter of 45 mm, height of 45 mm) with graphite as the main component, and the upper and lower ends of the mold were filled with graphite rods (inner diameter of 15 mm, height of 25 mm); after sintering, in order to remove the carbon on the surface of the sintered sodalite solidified body, 100-3000 mesh sandpaper was used for polishing, and the cylindrical sodalite solidified body (diameter of 15 mm, height of 4 mm) was polished to a certain depth to ensure that the carbon on its surface was removed.
[0104] The mechanical properties of the sodalite solidified body synthesized in Example 4 were evaluated:
[0105] 1. Hardness: A Vickers hardness tester (MHVD-1000 AP) was used to apply a force of 0.3 kg within 10 s to test the surface hardness of the sodalite solidified body.
[0106] 2. Density: The density and porosity of the sodalite solid body were determined by the Archimedean method.
[0107] (1) After drying the cylindrical sodalite solid body at 70 °C for 24 h, the dry weight of the sodalite solid body at room temperature was measured on an analytical balance ( W 1 ), with an accuracy of 0.001 g;
[0108] (2) Place the dried sodalite solid body in boiling water for 2 h. After cooling to room temperature, measure the floating weight of the saturated sodalite solid body in water ( W 2 );
[0109] (3) Wipe the water off the surface of the sodalite solid body with a multi-layer gauze filled with water, and measure the wet weight of the saturated sodalite solid body in air ( W 3 );
[0110] (4) Calculate the actual density of the solidified sodalite according to the following formula ( d )、densification( D ) and porosity ( P ).
[0111]
[0112] in, d is the actual density of the solidified sodalite; W 1 is the dry weight of sodalite solid at room temperature; W 2 is the floating weight of the saturated sodalite solid body; W 3 is the weight of saturated sodalite solid in air; WDT is the density of water at room temperature, which is 0.9982 g / cm 3 (20℃).
[0113]
[0114] in, D is the degree of densification of the sodalite solidified body; d is the actual density of the solidified sodalite; d 0 is the theoretical density of sodalite, which is 2.25 g / cm 3 .
[0115]
[0116] in, P is the porosity of the sodalite solid body, W 1 is the dry weight of sodalite solid at room temperature; W 2 is the floating weight of the saturated sodalite solid body; W 3 is the weight of saturated sodalite solid in air.
[0117] The mechanical properties evaluation results of the sodalite solidified body synthesized in this example are as follows: Fig.11 , 12 As shown in the figure, it can be seen that the density of the sodalite solidified body synthesized in this embodiment is more than 94%, the density is less than the theoretical density, and the hardness can reach up to 416HV. At the same time, the inventors have found that the density of the sodalite solidified body synthesized according to the steps of this embodiment using 35% and 45% radioactive waste salt by mass is more than 94%, and the hardness exceeds 350 HV.
[0118] In summary, the present invention grinds, sieves and sinter the solidified precursor obtained by heating 4A zeolite powder, radioactive waste salt, alkali metal chloride salt and dispersant to obtain a sodalite solidified body. In this method, the amount of 4A zeolite used is small, and the radioactive waste salt coverage rate is as high as 45%, the fixed amount of radioactive element chloride is as high as 15.183%, and the process operation is simple; the synthesized sodalite solidified body has strong thermal stability and high mechanical hardness, and the normalized leaching rate after immersion in 90°C water for 28 days is less than 5 x 10 -4 g / (cm 2 ·d) The sodalite solidified body can be stored geologically for a long time, effectively reducing the risk of migration, diffusion and leakage of radioactive substances.
[0119] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt, characterized in that: The following steps are involved: (1) mixing solid raw materials including 4A zeolite powder, radioactive waste salt, and alkali metal chloride salt with a dispersant, and then heating and drying to obtain a solidified precursor; wherein the mass ratio of the 4A zeolite to the alkali metal chloride is (3-5):1; and the mass percentage of the radioactive waste salt in the total weight of the solid raw materials is 15%-45%; (2) Grinding, sieving, and sintering the solidified precursor to obtain a sodalite solidified body.
2. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The heating treatment is performed at a temperature of 60 to 100°C and for a time of 6 to 12 hours.
3. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The radioactive waste salt includes radioactive waste salt of electrolytic reduction salt LiCl-Li2O system or electrolytic refining salt LiCl-KCl system.
4. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The liquid-to-solid ratio of the solid raw material to the dispersant is (4-6):
1.
5. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The sintering temperature is 600-900°C and the sintering time is 2-12 h.
6. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The alkali metal chloride salt is one or more of lithium chloride, sodium chloride and potassium chloride.
7. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The dispersant is one or more of water, ethanol and acetone.
8. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The particle size of the 4A zeolite powder is within 1 nm.
9. The method for synthesizing sodalite from 4A zeolite and in-situ simultaneous solidification of radioactive waste salt according to claim 1, characterized in that: The specific steps are as follows: (1) 4A zeolite was ball-milled at 200 r / min for 4 h with a ball-to-material ratio of 10:1 and passed through a 0.1 nm sieve to obtain powder; (2) 4A zeolite powder, radioactive waste salt, alkali metal chloride salt and dispersant are mixed uniformly at a liquid-to-solid ratio of (4-6):1, and heated in a water bath at 60-100 °C for 6-12 h. The resulting slurry is dried in an oven with forced air for 15-30 h to obtain a solidified precursor; (3) The solidified precursor was ground in an agate mortar for 30 min and then passed through a 0.1 mm sieve. The solidified precursor powder was sintered at a temperature of 600-900 °C for 2-12 h to obtain a sodalite solidified body.
10. The sodalite solidified body synthesized by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing sodalite by utilizing high-alumina fly ash
CN105858674A
Sodalite-based ceramic solidification method for radioactive iodine waste
CN111863304A
Solidification method of radioactive molten salt waste
CN115547536A
Method for gradient recovery of rare metals from coal gangue and synchronous synthesis of sodalite
CN117625950A
Method to synthesize dense crystallized sodalite pellet for immobilizing halide salt radioactive waste
US5340506A
Cited By
Method for synthesizing sodalite and solidifying and stabilizing harmful metal nuclide through hydrothermal method and application
CN120771829A